Prevalence of Clostridium difficile Infection in the Hematopoietic Transplantation Setting: Update of Systematic Review and Meta-Analysis - Luo, Ying; Zhang, Sumei; Shang, Hua; Cui, Weitong; Wang, Qinglu; Zhu, Bin (Frontiers in cellular and infection microbiology, 2022)
Hematopoietic stem cell transplant (HSCT) recipients are vulnerable to Clostridium difficile infection (CDI) due to risk factors such as immunosuppression, antimicrobial use, and frequent hospitalization. We systematically searched PubMed and Embase to screen relevant studies from April 2014 to November 2021. A meta-analysis was performed to identify the association between CDI and hematopoietic transplantation based on the standard mean difference and 95% confidence intervals (CIs). Among the 431 retrieved citations, we obtained 43 eligible articles, which included 15,911 HSCT patients at risk. The overall estimated prevalence of CDI was 13.2%. The prevalence of CDI among the 10,685 allogeneic transplantation patients (15.3%) was significantly higher than that among the 3,840 autologous HSCT recipients (9.2%). Different incidence rates of CDI diagnosis over the last 7 years were found worldwide, of which North America (14.1%) was significantly higher than Europe (10.7%) but not significantly different from the prevalence among Asia (11.6%). Notably, we found that the estimated prevalence of CDI diagnosed by polymerase chain reaction (PCR) (17.7%) was significantly higher than that diagnosed by enzyme immunoassay (11.5%), indicating a significant discrepancy in the incidence rate of CDI owing to differences in the sensibility and specificity of the detection methods. Recurrence of CDI was found in approximately 15% of the initial patients with CDI. Furthermore, 20.3% of CDI cases were severe. CDI was found to be a common complication among HSCT recipients, displaying an evident increase in the morbidity of infection.